PENGARUH MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING TERHADAP HASIL BELAJAR SIMULASI DIGITAL - Putri Irma Delianti; Elfi Tasrif; Ika Parma Dewi (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2018)
This research aimed to analyze the difference of learning outcomes by using Student Facilitator and Explaining model and direct learning model on Digital Simulation subject at class X TKJ SMKN 1 Tilatang Kamang. The problem in this study was the student learning result which were still under KKM on Digital Simulation subjects at SMKN 1 Tilatang Kamang. Type of this research was Quasi Experiment. The sample was taken through Probability Sampling technique. The research samples were class X TKJ A  and class X TKJ B. Class X TKJ A as sample for experiment class using Student Facilitator and Explaining  model and class X TKJ B as sample for control class using direct learning model. Data analyzed based on post-test experiment class and control class, then analyzed for normality test, homogeneity test and hypothesis test. From the experimental class, the research results obtained an average of 82.47, while the control class was averaged of 76.94. Result of hypothesis calculation at significant level α = 0,05 found tcount> ttable that is 1,78> 1,699, because tcount was bigger than ttable, so null hypothesis (H0) was rejected and alternative hypothesis (Ha) was accepted. It can be concluded at the real level that this study showed that Student Facilitator and Explainingmodel gave significant effect on students learning results of Digital Simulation at class X TKJ in SMKN 1 Tilatang Kamang. Therefore, the Student Facilitator and Explaining model is better than the direct learning model.Keywords: Student Facilitator and Explaining Model,Direct Learning Model, Learning outcomes, Experiment Class, Control Class.